2019
DOI: 10.1136/bmjopen-2019-032338
|View full text |Cite
|
Sign up to set email alerts
|

Participating in core outcome set development via Delphi surveys: qualitative interviews provide pointers to inform guidance

Abstract: ObjectivesTo explore participants’ views of Delphi surveys in core outcome set (COS) development.Study design and settingPatients and health professionals (n=24) from seven recently concluded COS studies that had involved a Delphi survey took part in semistructured qualitative interviews (telephone and email exchange). Interviews explored participants’ understanding of COS and their experiences of the Delphi survey. Analysis was thematic.ResultsSeveral interviewees had previously participated in two or more CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Our review indicates that the 1–9 scoring system is the most commonly used system in COS studies that include patients; however, this scoring system is used in the DelphiManager software, and the large number of electronically delivered studies that reported using this software may, therefore, have influenced this finding. Biggane et al 7 interviewed patients retrospectively about their experience of participating in a Delphi survey, noting that while there are statistical considerations influencing the choice of scoring scales, patients can have differing views on the scales used. While some patients in their study preferred the 1–9 scoring scale, others struggled to use it, indicating the need for additional support and guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review indicates that the 1–9 scoring system is the most commonly used system in COS studies that include patients; however, this scoring system is used in the DelphiManager software, and the large number of electronically delivered studies that reported using this software may, therefore, have influenced this finding. Biggane et al 7 interviewed patients retrospectively about their experience of participating in a Delphi survey, noting that while there are statistical considerations influencing the choice of scoring scales, patients can have differing views on the scales used. While some patients in their study preferred the 1–9 scoring scale, others struggled to use it, indicating the need for additional support and guidance.…”
Section: Discussionmentioning
confidence: 99%
“…There are several challenges in including patient participants in COS, and indeed there are indications some COS developers ‘problematise’ patient participation, 6 highlighting, for example, the tendency for patients to rate many outcomes highly. Biggane et al 7 found that patients without prior experience of Delphi surveys expressed difficulty understanding both the purpose of the COS and particular aspects of the surveys. Young and Bagley 8 called for further research exploring how patient input is currently being sought in COS studies and to understand more about the challenges of including and engaging patients in COS development.…”
Section: Introductionmentioning
confidence: 99%
“…A modified Delphi technique was used to develop a minimal standard outcome set. The Delphi technique is an iterative multi stage process to actively transform opinion into group consensus [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains unclear which rating scale is the most appropriate for use in the Delphi phase of a COS development study. Qualitative interviews reported mixed feedback from user experience of different rating scales [ 13 ] and only one study has compared the use of two different rating scales, a 3-point and a 9-point scale, for rating preliminary outcomes [ 14 ]. The authors of this study reported that the use of the 9-point rating scale resulted in almost twice as many outcomes being rated as important compared with the 3-point rating scale in the first Delphi round.…”
Section: Introductionmentioning
confidence: 99%